2014
DOI: 10.1111/bjd.12841
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of formalin-fixed Mohs surgery and haematoxylin and eosin stains with control contralateral biopsies for lentigo maligna: 5-year follow-up results

Abstract: The use of Slow Mohs formalin-fixed tissue and H&E section staining, even with comparator biopsies, does not provide sufficient discrimination to identify residual disease confidently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
4
22
0
Order By: Relevance
“…Also, many features of LM can be seen in chronically actinically damaged skin, including confluent melanocytes and adnexal extension, which can be highlighted by immunostains [47]. For these reasons and others, accuracy of diagnosis of LM and LMM on frozen en face sections has been questioned [48,49]. Despite these potential pitfalls, the majority of recurrence rates have been reported in the range of <1-6.3%, with an isolated smaller study showing 33% recurrence [40,42,50].…”
Section: Treatmentmentioning
confidence: 99%
“…Also, many features of LM can be seen in chronically actinically damaged skin, including confluent melanocytes and adnexal extension, which can be highlighted by immunostains [47]. For these reasons and others, accuracy of diagnosis of LM and LMM on frozen en face sections has been questioned [48,49]. Despite these potential pitfalls, the majority of recurrence rates have been reported in the range of <1-6.3%, with an isolated smaller study showing 33% recurrence [40,42,50].…”
Section: Treatmentmentioning
confidence: 99%
“…Early detection and adequate treatment with negative margins is important prior to progression to invasive melanoma. It has been well-established in the dermatology literature that standard 5 mm margins are inadequate for complete margin control in large series of LM [11,[15][16][17][18]. In a previously published series from our institution utilizing the same staged surgical technique, the margins required for clearance of LM was 7.1 mm, and for LMM was 10.3 mm [9].…”
Section: Discussionmentioning
confidence: 93%
“…Lawrence et al . showed that the use of slow‐Mohs formalin‐fixed tissue and H&E section staining, even with site‐matched contralateral biopsies, does not provide sufficient discrimination to identify residual disease confidently . However, they did not perform immunohistochemistry …”
Section: Reportmentioning
confidence: 99%
“…9 Lawrence et al 10 showed that the use of slow-Mohs formalin-fixed tissue and H&E section staining, even with site-matched contralateral biopsies, does not provide sufficient discrimination to identify residual disease confidently. 10 However, they did not perform immunohistochemistry. 10 Our data on LM/LMM is in line with the results reported by Paul and Gernand, 9 showing that the frequency of peritumoural melanocytes is increased compared with healthy skin.…”
Section: Reportmentioning
confidence: 99%
See 1 more Smart Citation